Three-dimensional numerical analysis of geocell reinforced shell foundations - Ari, Abdulmuttalip; Misir, Gizem (ELSEVIER SCI LTD, 2021)
The effects of geocell reinforcement on the behavior of shell foundations were studied using PLAXIS 3D finite element software. For this purpose, conical and pyramidal geometries were adopted as shell foundations. The real honeycomb shape of geocell and rigid body behavior of shells were simulated in PLAXIS 3D. The numerical models for shell foundations and geocell reinforced foundations were separately validated using several laboratory studies in the literature. The validated models were extended to the shell foundations resting on geocell reinforced sandy beds. The inclusion of geocell-reinforcement provided more than 70% reduction in the settlement of pyramidal and conical shell foundations. The stress transferred to the sand beds were reduced and distributed a wider area compared to the unreinforced cases. The maximum improvement in the bearing capacity and the settlement were observed in the case of conical shell foundation. The effect of adopted geocell and shell configuration on the foundation behavior was also analyzed for realistic prototype foundation size.
Keywords: Geocell; Shell foundations; Reinforced soil; Numerical modelling; PLAXIS 3D; BEARING CAPACITY; UNPAVED ROADS; DESIGN METHOD; BEHAVIOR; SAND; PERFORMANCE; FOOTINGS; CONFINEMENT; STRENGTH; BEDS; Engineering; Geology